INTERACIVE ACTIVITIES IN THE PRESENATION IN LIGHT OF THE TYPE AND USING - KROTKY, Jan (Trends in education, 2009)
The article continues research in the sphere of the interactive and multimedia presentations. It was realized on the workplace of didactic and information technologies at the Faculty of Education in Plzen by the author of this article. The research and following analysis of the works together with results was partly publicized through the conference IGIP ``The Strategy of Engineering Education in the Reflection of the Contemporary Era'' 2009. This article deals with some aspects of the realized facts and brings them compactly and in a new view. The elaborate version including the supporting pictures and graphs can be find on the portal CDMVT. It was made for support of teaching of didactic and multimedia technologies at FPE ZCU.
Keywords: Didactic technologies; didactic technique; presentation; interactive presentation; interactive board; InterWrite; WorkSpace; CDMVT.